CSIS : An Expert Database System - Hj. Mohamed, Hasimah (1994)
Database models and systems can be made intelligent by adding knowledge and inferencing capability. The tools for knowledge representation and inferencing are provided within the context of expert systems. The inference and object-based knowledge representation concepts are related to the database concepts and hence a relational database can be closely integrated with a knowledge base. Objects and inheritance can be used as higher level structures in dealing with relational databases. Hierarchical representation can show clearly the objects relationship and also the inheritance.